Strategic complementarity in banks' funding liquidity choices and financial stability - André Silva (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2016)
This paper examines whether banks' liquidity and maturity mismatch decisions are affected by the choices of competitors and the impact of these coordinated funding liquidity policies on financial stability. Using a novel identification strategy where interactions are structured through decision networks, I show that banks do consider their peers' liquidity choices when determining their own. This effect is asymmetric and not present in bank capital choices. Importantly, I find that these strategic funding liquidity decisions increase both individual banks' default risk and overall systemic risk. From a macroprudential perspective, the results highlight the importance of explicitly regulating systemic liquidity risk.
Keywords: G20; G21; G28; 330; funding liquidity risk; financial stability; macroprudential policy